Effects of Whole-Body Vibration in Hematobiochemical and Hemogasometric Parameters in Adult and Elderly Healthy Dogs - Silva, Bruna Martins; Santos, Ivan Felismino Charas; Rahal, Sheila Canevese; Dadalto, Carmel; Nagai, Lais Rosa; Tsunemi, Miriam; Teixeira Neto, Francisco José; Mamprim, Maria Jaqueline (Acta Scientiae Veterinariae, 2020)
Background: Whole-Body Vibration (WBV) consists of mechanical vibration stimuli produced that propagate throughout the body by increasing the gravitational load. The WBV can increase muscle mass in dogs with muscular atrophy. As Whole-body vibration (WBV) can be used as exercise modality with no impact on the joints, the present study aimed to evaluate the effects of single session of WBV in hematobiochemical and hemogasometric parameters in adult and elderly healthy dogs. Materials, Methods & Results: Fourteen clinically healthy, neutered crossbreed male dogs, non-athlete were selected. The dogs were divided into two groups of seven dogs, according to the age group: Group I - adult dogs (GI): age between 12.0 and 84.0 months old; Group II - elderly dogs (GII): age above 84.0 months old. All dogs were submitted to a single session WBV by using a vibrating platform that delivered a vortex wave circulation as mechanical vibration. The WBV protocol used was 30 Hz frequency (3.10 mm peak displacement; 11.16 m/s2 peak acceleration; 0.29 m/s velocity), then 50 Hz (3.98 mm peak displacement; 39.75 m/s2 peak acceleration; 0.62 m/s velocity), and lastly 30 Hz (3.10 mm peak displacement; 11.16 m/s2 peak acceleration; 0.29 m/s velocity) for 5-min between de frequencies. The hematobiochemical and hemagasometric parameters were evaluated at 1-min before the WBV session (1PRE), 1-min after the WBV session (1POST), 120-min (120POST) and 24 hours after the WBV session (24hPOST). The dogs accepted well the vibration stimulus, however, elderly dogs weighting above 30 kg were more likely to sit down with increased frequency from 30 to 50 Hz. No variations of food and water intakes and gastrointestinal changes were observed after the WBV session. Hemoglobin values showed significant decrease (P = 0.0312) between 1PRE and 1POST in elderly dogs. A significant decrease (P = 0.0453) was observed in alanine aminotransferase values between 120POST and 14hPOST in adult dogs. Creatinine values had a statically decrease (P = 0.0173) between 1PRE and 24hPOST in adult dogs. However, these values remained within the reference range for dogs. Discussion: According to the literature, there are no studies related to the effects of WBV in haematobiochemical and hemogasometric parameters in adult and elderly dogs. No deleterious effects regarding to a single session of WBV were observed, however harmful effects were observed in human patients. The elderly dogs with body mass above 30 kg tried to sit during the increased frequency from 30 to 50 Hz, which was associated with the pressure exerted in their paws. No significant differences were observed in erythrogram and leukogram parameters except for hemoglobin values. Significant decline was observed in hemoglobin values in adult Beagle dogs; and were associated with hemolysis. The significant decrease in alanine aminotransferase and creatinine values did not have clinical significance. No significant alterations were identified in hemogasometric parameters but slight increase in pH values was observed in horses subjected to a 60 km run, and was associated to the loss of Cl ions in sweat. The single session of WBV by using a vibrating platform that delivered a vortex wave circulation, at 30 and 50 Hz frequencies for 5 min did not induced significant changes in hematobiochemical and hemogasometric parameters in adults and elderly healthy dogs.